Bisphenol A and Metabolic Syndrome: Results from NHANES. (28th November 2012) - Teppala, Srinivas; Madhavan, Suresh; Shankar, Anoop
Abstract : Background . Bisphenol A (BPA) is detected in the urine of > 95% of US adults. Recent evidence from population-based studies suggests that BPA is associated with individual components for metabolic syndrome (MetS). However, no previous study has examined the direct association between BPA and MetS. Methods . We examined 2, 104 participants from the National Health and Nutrition Examination Survey 2003–2008. The main outcome was the presence of MetS (n = 741 ). Results . Increasing levels of urinary BPA were positively associated with MetS, independent of confounders such as age, gender, race/ethnicity, smoking, alcohol intake, physical activity, and urinary creatinine. Compared to tertile 1 (referent), the multivariable adjusted odds ratio (95% confidence interval) of MetS in tertile 3 was 1.51 (1.07–2.12); P -trend was 0.02. Conclusions . Urinary BPA levels are positively associated with MetS, in a representative sample of US adults and independent of traditional risk factors for MetS. Future, prospective studies are needed to confirm our findings.